The development of optical stiffness calibration software base on equipartition theorem, boltzman statistics and power spectrum density - Muhammad Yunus Hamid (Tanjong Malim, 2018)
The development of optical stiffness calibration software base on equipartition theorem, boltzman statistics and power spectrum density by Muhammad Yunus Hamid